Mídias digitais no ensino médio estadual de Minas Gerais - Priscila Rezende Moreira (2019)
This thesis analyzes the incorporation of digital media in Public High Schools in the State of Minas Gerais. As research methodology, we developed a study of qualitative nature, in which we carried out: (a) documentary research of the data concerning the computerized systems and digital equipment of the state schools of Minas Gerais; (b) semi-structured interview with 20 (twenty) teachers from 03 (three) state schools; (c) observations of classes in which the digital media were used by the interviewed teachers; and (d) observation of the type of use of this equipment by the schools. Furthermore, in this thesis, we verified Brazilian and Minas Gerais policies aimed at the acquisition of digital media in public schools and for the training of teachers to work with these technological resources; we presented the evolution and presence of technologies and media in society and for education; and we dealt with empirical research and the process of choosing the schools as the locus of our observations. Based on the analysis of field research, we verified the importance of public policies and government programs for the incorporation of digital media, both in the purchase of equipment, as well as in relation to teacher training and working conditions with technological resources in the educational environment. It is our intention that this study will contribute to the dissemination of reflections about the incorporation of digital media in Brazilian public schools, considering teacher training, school infrastructure and adequate digital educational content. We also hope this thesis motivates other studies on the use of educational technologies in High School.